Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1177/0003065110392228
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Projection, Superimposed On Simplistic Object Relations, Erodes Patient-Provider Relationships in High-Risk Pregnancy: an Empirical Investigation

Abstract: In an attempt to illustrate the relevance of psychoanalytic theory and research to behavior medicine, an empirical investigation was conducted of females treated at a high-risk pregnancy specialty clinic (N = 58). Drawing from psychoanalytic object relations theory, it was hypothesized and confirmed that use of projection as a defense mechanism during pregnancy, superimposed on simplistic object relations, predicted an erosion of patient-provider relationships during the pregnancy/postdelivery period. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…First and foremost, while social support can be defined from the traditional perspective of the spouse, the Psychology & Health 451 clinician may also serve as an additional or alternative source of support, particularly in high-risk pregnancy (Shahar et al, 2010). Identification of women in need of additional assistance following their delivery may improve their prognosis and reduce their chances of developing post-natal psychopathology following this surgical intervention.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…First and foremost, while social support can be defined from the traditional perspective of the spouse, the Psychology & Health 451 clinician may also serve as an additional or alternative source of support, particularly in high-risk pregnancy (Shahar et al, 2010). Identification of women in need of additional assistance following their delivery may improve their prognosis and reduce their chances of developing post-natal psychopathology following this surgical intervention.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…When one deals with normal samples, OR levels are predicted to be in the normal range for both groups, thus making the difference in all subscales harder to detect. Hence, there is need for a systematic examination of effects of all SCORS subscales in a wide variety of samples (Shahar, Porcerelli, Kamoo et al, 2010) Regarding the BORRTI, although we predicted that all four subscales would be associated with the ability to be in a relationship, only the AL subscale remained following T-tests and the final logistic regression, though all other subscales exhibited an insignificant trend. As with the SCORS, past studies have shown that all subscales should have pointed to the difference.…”
Section: Discussionmentioning
confidence: 77%
“…When one deals with normal samples, OR levels are predicted to be in the normal range for both groups, thus making the difference in all subscales harder to detect. Hence, there is need for a systematic examination of effects of all SCORS subscales in a wide variety of samples (Shahar, Porcerelli, Kamoo et al ., )…”
Section: Discussionmentioning
confidence: 99%
“…Only isolated studies have considered these possible associations, and even fewer studies have empirically investigated the possible intercorrelations. Shahar and colleagues ( 39 ) emphasized a possible link between impairments in mentalizing capacities and the use of immature defense mechanisms, such as projection. The authors stated that individuals with lower mentalization scores were restricted in their use of defense mechanisms, as they had struggles identifying their own mental states and those of others.…”
Section: Introductionmentioning
confidence: 99%
“…The authors stated that individuals with lower mentalization scores were restricted in their use of defense mechanisms, as they had struggles identifying their own mental states and those of others. This may be an explanation for why highly burdened individuals have a tendency to use immature defense mechanisms, as people are less likely to tap the full potential of their own mentalizing abilities in situations of high emotional burden ( 39 ). In one case study ( 40 ), the author presented a phobic patient who continuously used the inhibition of mentalization as a defense against mental threats.…”
Section: Introductionmentioning
confidence: 99%